Evaluation of the Implementation of the Kampung Tangguh Semeru Model in Handling Covid-19: Evaluasi Implementasi Model Kampung Tangguh Semeru dalam Penanganan Covid-19. - Dinariyanti, Surya; Rodiyah, Isnaini (Universitas Muhammadiyah Sidoarjo, 2023)
This qualitative research endeavors to assess the implementation of the Tangguh Semeru Village program in Gilang Village, Taman District, Sidoarjo Regency, with a particular focus on handling the COVID-19 pandemic. Employing a descriptive research approach, primary and secondary data were collected through observation, interviews, and documentation. Despite the overall effectiveness of the program, reluctance among some residents to report to the COVID-19 Task Force due to fear of social ostracism remains a challenge. The study reveals that human resource efficiency in the program is compromised, as volunteers' participation declines due to remote work commitments. Furthermore, issues related to the equitable distribution of COVID-19 vaccinations and the lack of firm sanctions for non-compliance with isolation measures highlight areas for improvement. The positive response from both village officials and residents underscores a potential for enhancing the program's responsiveness. This research calls attention to the need for targeted interventions to address these challenges, ensuring the equitable and efficient implementation of community-based COVID-19 response programs. Highlight : Social Stigma Challenges: The study identifies and addresses the reluctance of residents to report COVID-19 cases due to fear of social ostracism, emphasizing the crucial role of community perception in effective pandemic management. Human Resource Efficiency: Highlighting a decline in volunteer participation due to remote work commitments, the research underscores the importance of sustaining and optimizing human resources in community-based response programs. Equity in Vaccination Distribution: The findings shed light on disparities in the distribution of COVID-19 vaccinations, emphasizing the need for targeted interventions to ensure equitable access and coverage within the community. Keywords: Tangguh Semeru Village, COVID-19 Response, Community-based Programs, Implementation Evaluation, Equity in Pandemic Management